2010
DOI: 10.1002/cbdv.201000006
|View full text |Cite
|
Sign up to set email alerts
|

How to Produce a Chemical Defense: Structural Elucidation and Anatomical Distribution of Aplysioviolin and Phycoerythrobilin in the Sea Hare Aplysia californica

Abstract: We previously used bioassay-guided fractionation to identify phycoerythrobilin (1) and its monomethyl ester, aplysioviolin (2), as components in the ink secretion of a marine gastropod, the sea hare Aplysia californica, that act as chemical deterrents against predatory blue crabs. This was the first report of 1 as a natural product. Compound 2 was previously reported as a natural product from three species of Aplysia (A. fasciata, A. dactylomela, and A. parvula), but the reported structure and composition of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The ink of sea hares and two of ink's major components, APV and PEB (Kamio et al 2010a), are relevant and potent deterrents to sea catfish. Our behavioral studies show that sea catfish, which are sympatric to sea hares, rejected food or food-flavored pellets treated with biologically relevant concentrations of whole ink, APV, or PEB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ink of sea hares and two of ink's major components, APV and PEB (Kamio et al 2010a), are relevant and potent deterrents to sea catfish. Our behavioral studies show that sea catfish, which are sympatric to sea hares, rejected food or food-flavored pellets treated with biologically relevant concentrations of whole ink, APV, or PEB.…”
Section: Discussionmentioning
confidence: 99%
“…The relative retention times, peak heights and UV/ Visual spectra were considered sufficient for identification of APV and PEB for the purposes of analysis in this study. Kamio et al (2010a) combined NMR analysis with UV/ Visual Spectra and HPLC techniques to further study the composition of APV and PEB. Following HPLC separation, samples of the fractions containing APV and PEB were analyzed for free amino acid content (AminoAcids.com, St. Paul, MN USA), to ensure that any behavioral or electrophysiological response to these fractions was not due to free amino acids.…”
Section: Collection and Purification Of Sea Hare Secretionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our own experiments leading to this paper, we found that compounds such as capsaicin, menthol, allyl isothiocyanate and Nmethylmaleimide, which are known irritants and deterrents, were almost insoluble in ASW and were not pursued further because they tended to aggregate in big clumps, making it impossible for us to deliver them consistently (data not shown). Interestingly, although PEB and APV are equally potent, A. californica transforms the former into the latter by changing a carboxyl group into a methyl ester (Kamio et al, 2010b), a reaction that may make the molecule even less soluble in water.…”
Section: Why Wait So Long?mentioning
confidence: 99%
“…Dolabella auricularia collects molecules from the sea weeds in the sea and stores the compounds. Secretion of the ink from dolabella auricularia contains several molecules, such as aplysioviolin [4], dolabellin [5,6], auriside A and dolastatin 10 [7] (Figure 5). In the case of auriside A, synthesis of C1-C9 of the molecule was carried out with Meinwald reaction of alkyl propionate [8].…”
Section: Introductionmentioning
confidence: 99%